Efektivitas Media Realia dan Blok Pecahan Terhadap Kemampuan Berhitung Materi Pecahan Peserta Didik Sekolah Dasa - Dita Fauziyah, Suharno, Siti Kamsiyati (Universitas Sebelas Maret, 2019)
This study aims to determine the effectivity of realia media and fraction blocks toward fractional material numeracy. The population and sample used in this research is all fourth grade students of elementary school in cluster R.A. Kartini Teras Boyolali academic year 2017/2018. The sample of the research was done by random sampling, the selected samples are SD Negeri Banjarsari, SD Negeri 1 Teras, SD Negeri Barengan and SD Negeri 2 Teras. This research used quasi experimental research method with randomized control-group pretest-posttest design. Technique of collecting data using test and documentation method. The analysis technique that used is t-test with significance level 5%. The result that there are differences in the effectivity of fraction blocks and realia media with an average ratio of 76,125 and 72 and proven from the results of the t-test with significance level of 5% obtained -ttable < tcount < ttable (-1,993 < 1,254 < 1,993). The use of fraction blocks is more effective than realia media toward fraction material numeracy. Keywords : realia media, fraction blocks, fraction material numeracy